Clinicopathological study of gall bladder carcinoma: Our experience from Patan Hospital, Patan Academy of Health Sciences (Journal of Society of Surgeons of Nepal, 2019)
Introduction: Gall bladder carcinoma is not a common disease. The overall prevalence is low worldwide. It is a highly malignant tumor with a poor prognosis. The outcome of gallbladder carcinoma is poor, and the overall 5-year survival rate is less than 5%. The carcinoma gall bladder is 2-6 times more common in females compared to males and its incidence increases with increasing age. Aggressive surgical management and preoperative adjuvant therapy have helped to prolong survival in patients with gallbladder cancer. We conducted a study with an aim to evaluate the clinicopathological aspect of the disease in patients of gall bladder cancer managed in our surgical department.Methods: Data were recorded retrospectively by reviewing the charts of the patients who were diagnosed and treated for carcinoma gall bladder in Patan hospital from Aug 2017 to Aug 2019.Results: Thirty patients were included in the study. Twenty (66.7%) were female and ten (33.33%) were males. Age ranged from 36 to 83 years with the median age of presentation at 63.5 yrs. Curative treatment was possible in 43.33% of the patients, among them 12 had radical surgery and one had cholecystectomy alone for the T1a stage.  All other (56.6%) required palliative treatment. One patient developed liver metastasis within six months of radical excision.Conclusions: The majority of the patients present with an advanced disease which makes it less chance for curative surgical resection. Since only palliative care is possible in an advanced stage, early detection and curative treatment are advisable.